Modern dynamics of the health of the population of Ukraine in global dimension - Grebniak, N.P.; Taranov, V.V.; Fedorchenko, R.A. (Environment & Health, 2018)
Objective: We analyzed the population health of the population of Ukraine in comparison with the indicators of the European region and throughout the world.Materials and methods: The study was carried out on the basis of WHO data, annual reports of UNAIDS, the State Statistics Committee of Ukraine for 1990-2016. The assessment of the state of population health at the national, European and world levels was carried out according to WHO indicators (mortality, life expectancy, incidence, prevalence of diseases, medico-social factors) which main requirements are validity, specificity, sensitivity, reliability, representativeness, intelligibility, accessibility. We used analytical, statistical, system approach, comparative analysis trends methods.Results: The pronounced negative tendencies were established to be typical for the current state of population health of Ukraine's population. Medico-demographic situation is characterized by an extremely high mortality, a low level of life expectancy and a demographic aging of the population.Conclusions: The death rate of the population of Ukraine is significantly higher than the level in the European Region and is characterized by its growth last years, especially due to the infectious diseases and HIV/AIDS. A higher death rate in men and a low life expectancy are the gender specificities of mortality in the country. The high levels of the consumption of strong alcoholic beverages, the prevalence of smoking against the background of consistently low financing for health care are the national features of medico-social risk factors for the health of the population.
Keywords: health of the population of Ukraine; mortality; life expectancy; medico-social factors